The Effectiveness of Wallacea Net Operation as a Model for Implementing the Port State Measures Agreement in Indo-Pacific - Ema Nurhayati (Universitas 17 Agustus 1945 Semarang, 2026)
The Indo-Pacific region faces non-traditional maritime security threats, with Illegal, Unreported, and Unregulated (IUU) Fishing as a multidimensional problem that causes regional economic losses. Indonesia, as one of the largest archipelagic countries in the world, has implemented Wallacea Net Operation to protect its maritime sovereignty from the threat of IUU Fishing, but a comprehensive evaluation of its effectiveness is still limited. This study aims to analyze how the implementation of Wallacea Net Operation as a model for implementing PSMA in the Indo-Pacific region using normative legal research methods through literature studies. The results of the study show that Wallacea Net Operation has a strong historical and legal basis, starting from the Djuanda Declaration in 1957 to the ratification of PSMA in 2016. This operation represents the implementation of coastal state jurisdiction according to UNCLOS 1982 and has shown significant results in reducing IUU Fishing cases in Indonesian waters. However, implementation challenges remain related to limited resources, inter agency coordination, and regional diplomatic relations. Concrete recommendations from this study include harmonization of laws and regulations related to maritime security, increasing the capacity of surveillance technology, strengthening regional cooperation through the Indo-Pacific Fisheries Intelligence Network, intensifying maritime diplomacy to encourage ratification of the PSMA in more countries in the region, and developing effective public diplomacy strategies to legitimize ship sinking policies.